Blood Platelets Adhesion to an Intermetallic Сoating Made by SHS Using Magnetron Sputtering Ti-Ni-Ti Nano-Laminate - Baigonakova G. Gulsharat; Yasenchuk Yu. Yuriy; Marchenko E. Ekaterina; Gunther S. Sergey; Кокоrev О. Oleg; Zenkin S. P. Sergey Petrovich; Yuzhakov M. M. Mikhail Mikhaylovich (Biomedical and Industrial Applications. Oral Presentation, 2019)
Заглавие с экрана